2022
DOI: 10.3390/biomedicines10092088
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-Directed Therapies in Cancer

Abstract: The human ribosomes are the cellular machines that participate in protein synthesis, which is deeply affected during cancer transformation by different oncoproteins and is shown to provide cancer cell proliferation and therefore biomass. Cancer diseases are associated with an increase in ribosome biogenesis and mutation of ribosomal proteins. The ribosome represents an attractive anti-cancer therapy target and several strategies are used to identify specific drugs. Here we review the role of different drugs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 217 publications
(256 reference statements)
0
10
0
1
Order By: Relevance
“…8A-D ). As revealed by ORO staining, Etoposide, a classic inhibitor of DNA unwinding, as well as Acivicin and Streptonigrin, two inhibitors of ribosome biogenesis and assembly (38, 39), significantly impeded 3T3- L1 differentiation when administered during the first 48h or during the full process of differentiation ( Sup. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8A-D ). As revealed by ORO staining, Etoposide, a classic inhibitor of DNA unwinding, as well as Acivicin and Streptonigrin, two inhibitors of ribosome biogenesis and assembly (38, 39), significantly impeded 3T3- L1 differentiation when administered during the first 48h or during the full process of differentiation ( Sup. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…And ribosome biogenesis hyperactivation addiction in cancer cells is clear, by illustrating its numerous molecules as cancer treatments through impairing ribosome production [24] .In normal cells,ribosomes are involved in proliferating by synthesizing proteins, but in cancer cells,ribosomes are needed according to metabolic requirements. And what's more, previous study has reported that cancer cells express about nearly 10,000 different proteins [25] . Ribosome biogenesis can be a target in cancer cells because of three main reasons, rstly in certain cancer types and its cell populations,this process is highly active and essential,secondly several chemotherapy drugs have been already proven to exert their some pharmacological effects partly,through impairing ribosome biogenesis, and last but not the least blocking ribosome biogenesis can lead in a lot of cases to the activation of p53 [26] .…”
Section: Discussionmentioning
confidence: 98%
“…Consequent functional enrichment analysis of these four modules unveiled connections to pathways related to esophageal cancer progression, multiple research studies corroborate with these findings. Specifically, Module 1 has shown significant connections to translational elongation and ribosomal functions ( Figure 4A ; Temaj et al, 2022 ), Module 2 is linked to histone function, activation of matrix metalloproteinases, and interferon signaling ( Figure 4B ; Jiao et al, 2014 ; Mittal et al, 2016 ; Ozkan and Bakar-Ates, 2020 ), Module 3 is primarily associated with mRNA regulation ( Figure 4C ; Teng et al, 2022 ), and Module 4 is chiefly related to chemokine activity ( Figure 4D ; Nicolau-Neto et al, 2018 ). Each of these modules seems to have a unique role in the progression of esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%